Assessment of anorexia readiness syndrome and body image in female dancers from Poland and Germany - Ołpińska-Lischka, Marta (Journal of Education, Health and Sport, 2017)
Introduction:In recent years eating disorders have become an increasingly common problem, both in the media and in the scientific world, and the most dangerous form of these disorders is anorexia. Amongst patients with Anorexia Readiness Syndrome (ARS), there is an excessive tendency for physical activity and affected persons are increasingly developing into athletes. Therefore it is very important to control such behavior in physically active individuals. In psychology, a new phenomenon is investigated - An Anorexia Readiness Syndrome (ARS), which is considered a disease stage of full-blown anorexia. The problem of anorexia readiness syndrome and dancers body perception is poorly researched and its significance to the health of this group of people is extremely important. Aim: The purpose of this research was to find out how big is the difference of anorexia readiness syndrome and to find out the differences in the perception of their bodies in Polish and German dancers. Material and methods: Questionnaires on anorexia readiness syndrome (ARS) and body image were anonymously filled in by the dancers. The study was carried out on 156 dancers from Poland and Germany. Results: The results showed that most of the dancers were diagnosed with moderate to severe anorexia readiness syndrome. Only in the group of older Polish dancers didn’t occur an anorexic syndrome. The statistically significant differences in self-evaluation of body parameters were assessed in the assessment of: nose, face, breasts and physical condition. Conclusions: The results to determine the severity of anorexia readiness syndrome are not very optimistic and only data from the literature confirms that the dance environment is specific to the high risk of eating disorders.